Decolonizing design a cultural justice guidebook - Tunstall, Elizabeth (Cambridge, Massachusetts The MIT Press, 2023)
"Responds to the urgent call to decolonize design through powerful, incisive guidelines drawn from 15 years of lived experience. A transformative blueprint for repairing the harm caused by structural inequity through decolonizing not only our institutions, but also our thinking, and how to begin today"--Provided by publisher.
Putting Indigenous First -- Dismantling the Tech Bias in the European Modernist Project -- Dismantling the Racist Bias in the European Modernist Project -- Making Amends is More than Diversity, Inclusion, and Equity -- Reprioritizing Existing Resources to Decolonize.
Includes bibliographical references and index.
Keywords: Design -- Social aspects; Decolonization